Des séries de mouvements aux images du temps dans les séries, ou l’art d’analyser les fictions audiovisuelles - Jean-Pierre Esquenazi; Stéfany Boisvert (Communiquer)
This interview with Jean-Pierre Esquenazi (Université Lyon 3) focuses on his important contribution to the analysis of films, TV series, and popular culture. The article discusses his social semiotic approach for media productions, with its emphasis on audiences and interpretation. The interview also focuses on his methodology for the analysis of movements and “images of time” in films and series, which is directly inspired by Deleuze’s work. The discussion on TV series as an “art of time” also leads Esquenazi to reflect on the importance of adopting a normative approach when analysing series, and therefore to define them as works of art, in a context where the legitimacy of TV studies is still highly debated in academic circles.